Antidiabetic activity of Kabasura Kudineer Chooranam - P Harini; Vishnu Priya Veeraraghavan; J Selvaraj; R Gayathri; S Kavitha (Wolters Kluwer Medknow Publications, 2022)
One of the traditional plants used in Siddha medicine is Kabasura Kudineer Chooranam. It is said to possess antiaging, life-strengthening, and disease-preventing activities that have an enormous influence on health care. It has significant therapeutic potential and ethnobotanical significance. The aim of this study is to investigate the antidiabetic activity of Kabasura Kudineer Chooranam. The antidiabetic potential of Kabasura Kudineer Chooranam was determined in vitro using established methods such as alpha-amylase and alpha-glucosidase activity. We used one-way ANOVA to see the statistical difference among the groups. The significance thresholds were considered at the P < 0.05 level. In comparison with the healthy group, the extract showed a significant antidiabetic effect. The proportion of inhibition increased as the concentrations increased. Previous studies established the antiviral, anti-inflammatory, analgesic, antifungal, antioxidant, antibacterial, hepatoprotective, antiasthmatic, immunomodulatory, and antipyretic effects of Kabasura Kudineer or Choornam. The current findings demonstrated that the Chooranam has good antidiabetic action at a significant concentration. Plant-based products have recently proven to be effective and economical antidiabetic items.